An Inquiry-Based Learning Module for General Mathematics: Its’ Development and Evaluation - Lumabit, April Mae C.; Sagge, Jr., Roberto G. (Future Science / FSH-PH Publications, 2023)
The goal of this developmental research was to develop and evaluate an Inquiry-Based Learning Module for General Mathematics for Grade 11 students. It was conducted at two secondary schools with one hundred forty-one Grade 11 students and four mathematics teachers as respondents. The study used the descriptive-evaluative method to describe and evaluate the developed module using the questionnaire-checklist in gathering data. The development of the module utilized the modified model by Borg and Gall, which includes the inspection of the curriculum guide, planning, product development and designing assessment instrument, development of the instructional materials, validation of mathematics teachers and experts, revisions, limited trial to students and the finalization of the instructional material. The respondents were asked to evaluate the worktext on the following aspects: objectives, contents, activities, style and presentation, organization, creativity, and assessment. The result shows that the developed module with respect to objectives, contents, activities, style and presentation, organization, creativity, and assessment was verbally interpreted as